Lending Structure And Market Risk Exposures: The Malaysian Case - Abdul Rahman, Aisyah (Asian Academy of Management (AAM), 2009)
This study addresses the linkages between lending structure and market risk exposure. The influence of lending structure is analysed by four measures: the real estate lending, the specialisation index, the short-term lending stability, and the medium-term lending stability. Our findings show that lending structure to some extent affects the market risk exposure to some extend. At the same time, listed bank holding companies showed higher levels of market risk during and after the 1997 Asian financial crisis. Meanwhile, the desired effect of bank mergers in terms of reducing market risk exposure did not materialise in this study. Thus, the findings of this study posits at least two implications; (1) policy makers should react accordingly in the decision-making process towards achieving the expected result of the monetary policy transmission mechanism, and (2) banks and investors should account the impact of lending structures in addition to the significance effect of loan expansion and management efficiency when determining market risk exposure of bank holding companies.